Trinidad Carnival on Stage - Norton, Noel (Bon Genie Ltd, Port of Spain, Trinidad, 2009)
Description on the back of postcard: “Bands of carnival players are judged on stage during 2 days of excitement, steelpan and brilliant colour in Trinidad’s fantastic carnival.”
Colour: Coloured, Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Carnival; Carnival costumes